2006
DOI: 10.1002/eji.200535468
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term persistence of hepatitis B surface antigenand antibody induced by DNA‐mediated immunization results in liver and kidney lesions in mice

Abstract: DNA-mediated immunization has been recognized as a new approach for prevention and treatment of hepatitis B virus (HBV) infection. However, the side effects of this approach have not been well described. Here we report that DNA-mediated immunization by intramuscular injection of plasmid DNA encoding HBV surface antigen (HBsAg) induced long-term persistence of HBsAg and HBsAg-specific antibody (anti-HBs) in the sera of the immunized BALB/c mice and resulted in liver and kidney lesions. The lesions persisted for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…Data from animal studies showed that DNA vaccines could increase the production of anti-DNA autoantibodies but did not increase disease severity in lupus-prone animals nor induce autoimmunity in healthy animals [18,19]. Injection of mice with a plasmid encoding hepatitis B surface antigen (HBsAg) induced liver and kidney damage that was explained by the prolonged expression of HBsAg resulting in the formation of immune complexes [20]. Parker et al failed to find evidence of pathological changes after repeated injections of DNA in mice or rabbits [21].…”
Section: Dna Vaccine Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…Data from animal studies showed that DNA vaccines could increase the production of anti-DNA autoantibodies but did not increase disease severity in lupus-prone animals nor induce autoimmunity in healthy animals [18,19]. Injection of mice with a plasmid encoding hepatitis B surface antigen (HBsAg) induced liver and kidney damage that was explained by the prolonged expression of HBsAg resulting in the formation of immune complexes [20]. Parker et al failed to find evidence of pathological changes after repeated injections of DNA in mice or rabbits [21].…”
Section: Dna Vaccine Safetymentioning
confidence: 99%
“…Over the last 15 years, DNA vaccines have proved effective in animal models including against HIV, malaria and influenza [1]. DNA vaccines have been extensively evaluated in humans with a recent review identifying 72 Phase I, 20 Phase II and two Phase III human trials [2]. DNA vaccines have a good safety record, with the most common adverse reactions being mild-moderate inflammation with associated pain, redness and swelling at the injection site [1].…”
mentioning
confidence: 99%
“…It was reported in experiments with transgenic mice that WKH GHSRVLWLRQ RI LPPXQH FRPSOH[ DQWLJHQDQWLERG\ VSHFL¿F against HBsAg could cause damage at liver and kidney levels. 9 Based on all the above evidences, the present work explore with more details safety aspects related with the nasal/parenteral administration of the therapeutic vaccine candidate NASVAC. With that purpose we simulated the environment of a chronic patient that develops a potent immune response against the surface and nucleocapsid antigens of HBV after the administration of said vaccine + T lymphocytes.…”
Section: +0641and7%6+10mentioning
confidence: 99%
“…or intramuscular injection (i.m.) administration (Nishikawa et al, 1998;Zi et al, 2006). Our results with naked plasmid DNA vaccination, via both i.v.…”
Section: Discussionmentioning
confidence: 55%